The role of superior varieties in increasing rice productivity on tidal lands in South Sumatra - Niluh Putu Sri Ratmini; Pandu Hutabarat; Siti Khusniyati (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2024)
The development of tidal land as agricultural land is one opportunity to meet food needs. The study aimed to determine the contribution of superior varieties in increasing tidal rice productivity in South Sumatra. The research was conducted in Banyuasin Regency in 2021 using survey and interview methods. The number of sub-districts where sampling was taken was 9 sub-districts which are representative of low tide land. The data collected in this research were the results of harvested dry grain (tiles), the varieties used, the type and dose of fertilizer used, planting methods and cropping index. Apart from primary, secondary data was also collected as supporting data in the form of land area for each region and climatic conditions. The data taken was tabulated and analyzed descriptively. The research results show that the productivity level of superior rice varieties is higher than the district average productivity. Increasing productivity by applying superior varieties reaches 1.5 t/ha.